If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5r + 6 = 3r + 14 Reorder the terms: 6 + 5r = 3r + 14 Reorder the terms: 6 + 5r = 14 + 3r Solving 6 + 5r = 14 + 3r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-3r' to each side of the equation. 6 + 5r + -3r = 14 + 3r + -3r Combine like terms: 5r + -3r = 2r 6 + 2r = 14 + 3r + -3r Combine like terms: 3r + -3r = 0 6 + 2r = 14 + 0 6 + 2r = 14 Add '-6' to each side of the equation. 6 + -6 + 2r = 14 + -6 Combine like terms: 6 + -6 = 0 0 + 2r = 14 + -6 2r = 14 + -6 Combine like terms: 14 + -6 = 8 2r = 8 Divide each side by '2'. r = 4 Simplifying r = 4
| a=h/m | | 1x-4=-4x+41 | | 6x^2-16x-13=0 | | -18v^7+9v^4+15v^3+12v^2=0 | | 6x+45=-3x | | -4y+7y=11y | | 0=9/4x-9 | | 5=9/4x-9 | | 2=9/4x-9 | | 1=9/4x-9 | | -16=k-12 | | 3x-12=-2x+2 | | 8-8c-8c-4b-4b= | | 5x-20=-3x+20 | | x-5-7=2(x+2) | | 12(x-3)-32=5(13+x) | | 92+53+115+2x+3x=540 | | 0=7/6x+6 | | 2(-8+6x)=-4 | | 2(5x+7)=-42+26 | | 5(-6x+3)=15 | | 1x-3=-4x+37 | | 1=7/6x+6 | | -1(5x-3)=1 | | 2x+42=-4x | | -5x+6-x=-6 | | 2x-8=-3x+22 | | 6x+7(2-x)=14-9x-8 | | Y=7/6(0)+6 | | 3x-9=-4x+19 | | 1x-4=-4x+36 | | 3(x+5)(x-10)=7 |